Litter Production of Cocoa-Based Agroforestry in West Sumatera, Indonesia - Santhyami Santhyami; Adi Basukriadi; Mufti Petala Patria; Rochadi Abdulhadi (PLANTA TROPIKA, 2022)
Litter is a fragment of aboveground carbon stocks, a vital bridge to the belowground carbon cycle. Land conversion to agricultural purposes will affect litter production. This study aimed to compare the litter production of natural forests with cocoa-based agroforestry systems (AFS) in West Sumatra. Litter production was measured in five different types of ecosystems, namely natural forest (NF), cocoa-rubber-based AFS (CR), multistrata cocoa-based AFS (CM), cocoa-coconut-based AFS (CC), and cocoa monoculture (M). This study is quantitative research with the collection method. The difference in litter production between the five ecosystems observed was tested using ANOVA parametric statistical method. Litter was collected monthly for one year in which litter traps were evenly distributed in each research plot. Ecosystems of NF and M produced the highest annual litter (6.04 Mg ha-1 and 4.65 Mg ha-1 respectively), while CR produced the lowest one (2.52 Mg ha-1). Although this study did not perform comprehensive modeling of decomposition dynamics, the measurement of annual litter production can provide a further understanding of the dynamics of ecosystem carbon, especially in cocoa-based agroforestry.